Berkeleyomyces rouxiae is a causal agent of root rot complex on faba bean (Vicia faba L.) - Long, Juechen; Wu, Wenqi; Sun, Suli; Shao, Yang; Duan, Canxing; Guo, Yanping; Zhu, Zhendong (Frontiers in Plant Science, 2022)
Faba bean (Vicia faba L.) is an important food and feed legume crop in the world. The root rot complex caused by various pathogens is a main constraint in faba bean production. In April 2021, a severe disease of faba bean with symptoms of black necrosis on roots occurred in experimental fields at the Linxia Institute of Agricultural Sciences, Gansu Province, China. This study aimed to identify the pathogen and evaluate the resistance of faba bean cultivars. The pathogen was isolated from infected soils, and five representative isolates were identified as Berkeleyomyces rouxiae based on morphological characteristics, pathogenicity, and molecular phylogenetic analyses. A host range test showed that chickpea, common bean, cowpea, mung bean, rice bean, lentil, and hyacinth bean were susceptible hosts of the faba bean isolate, whereas adzuki bean, pea, and soybean were non-susceptible hosts, and maize and wheat were non-hosts. Identification of resistance among 36 faba bean cultivars was carried out, and six cultivars were found to be moderately resistant to B. rouxiae. In this study, we first reported black root rot on faba bean caused by B. rouxiae, confirmed and expanded the host range of B. rouxiae, and identified resistant faba bean cultivars.